posted by .

I only have 1 hour to get this question answered. Thank you in advance. I need a quadratic equation in the variable x given the solutions:
-7 sqrt 7, and 7 sqrt 7
This needs to be in the standard form of ax^2+bx+c=0.

For a quadratic equation with given zeroes z1 and z2, the equation is:
(x-z1)(x-z2)=0
In the given case, z1=-7√7 and z2=7√7.
Expand and simplify the resulting expression on the left-hand-side, and equate coefficients of powers x², x and constant term to get the values of a, b and c.

I gave you response to a similar question, except that I forgot the variable x, which should have read:
x² -5√5x -30 = 0

see:

http://www.jiskha.com/display.cgi?id=1289541351

I understand, although mathlab checked it wrong and gave me this problem. I SIMPOLY do not understand this when it comes to radicals. And furthermore mathlab has a habit of checking problems wrong when they are indeed right.I understand how to FOIL, I just do not know how to work the radicals, CAN YOU PLEASE HELP ME!!!! This is due in 1 hour. Thank you so much!!!

And you are paying for Mathlab?

Just follow MathMate instructions and set it as
(x - 7√7)(x+7√7) = 0
looks like the difference of squares pattern, so ...

x^2 - 343 = 0

then
a=1
b=0
c=-343

try that as input

## Similar Questions

1. ### MATH

I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct?

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
3. ### math

solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the quadratic formula to solve for x and express those solutions in a+bi form. x = [-b + or - sqrt(b^2 - 4ac)]/2a Note: sqrt = square root. a = 2, b = 3, and c = 8 …
4. ### math,help,algebra I

I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-) …

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
6. ### Calculus

Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
7. ### algebra

write a quadratic equation having the given numbers as solutions 6 - sqrt(2) , 6 + sqrt(2) thanks for any help
8. ### Algebra

I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) d.y = sqrt(-x-1) …